Ictal magnetoencephalographic discharges from elementary visual hallucinations of status epilepticus. Issue 4 (1st April 2003) - Oishi, M; Otsubo, H; Kameyama, S; Wachi, M; Tanaka, K; Masuda, H; Tanaka, R
Abstract : Purpose: To report the rare opportunity to study ictal magnetoencephalography (MEG) in a 26 year old man with simple partial status epilepticus that presented as elementary visual hallucinations (EVHs) in the right upper visual field. Methods: The patient described his EVHs as "snowing on TV, " "flickering lights, " and "rotating coloured balls" that continued for several days. MEG and simultaneous EEG were recorded twice: during an episode of EVHs (ictal recordings) and after EVHs were controlled by medications (interictal recordings). Results: During EVHs, MEG showed continuous periodic epileptiform discharges over the left posterior superior temporal region, while simultaneous EEG showed rhythmic theta waves and sporadic spikes over the left temporal region. The MEG discharge consisted of a three phase spike complex. Equivalent current dipoles (ECDs), modelled from spike complexes, localised in the left superior temporal area. After drug treatment controlled the EVHs, interictal MEG and EEG showed rare spikes over the same left temporal region. The average ictal ECD moment (mean (SD)) (128.7 (32.8 nAm)) was significantly weaker than the average interictal ECD moment (233.0 (63.9) nAm) (p<0.05). Conclusions: The continuous, periodic, and clustered discharges seen on ictal MEG were the sources of EVH. The weaker ictal ECD sources were frequently not detected by scalp EEG, while the stronger interictal sources, presumably originating from an extensive interictal zone, were sufficiently large to be seen as EEG spikes.